(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the effectiveness of positive communication solutions to reduce the risk in milk and dairy products for children under 36 months and pregnant women. Subjects and methods: Community intervention study, with control group. Conduct active communication for 543 pregnant women, 543 mothers with children under 36 months (or caregivers) in 4 intervention wards. Evaluate the effectiveness of the intervention after 12 months, with comparison of the control group. Results: The effectiveness of intervention with knowledge is 770.06%, practice is 235.5% (for pregnant women); for mothers with children under 36 months, knowledge is 376.9%, practice is 260.9%. The intervention helped increase the use of milk and dairy products in pregnant women and children under 36 months. The intervention has also resulted in a significant reduction in the incidence of diarrhea and malnutrition in young children. Conclusion: Active communication solutions have been proven effective in reducing the risk in milk and dairy products intended for children under 36 months and pregnant women.